A lifeworld approach to the pupils' general development in school. Issue 4 (1st October 2020) - Skibsted, Else
Abstract: The pupils' general development is a core value in the legal framework and purpose of the Nordic schools. In spite of various attempts to specify the concept both theoretically and pedagogically, it is still considered an abstract and broad concept that lacks content and relation to the pupils' lifeworlds. The present article demonstrates that it is possible to identify a number of lifeworld challenges and to describe and operationalise these using Life Psychology. This approach forms the theoretical basis for the formation of a categorial pedagogy aimed at the pupils' general development which builds on concrete aspects of the pupils' lifeworlds on the one hand and, on the other hand, is related to various generic human life tasks and skills that the pupils must achieve to comprehend and manage the world and themselves. Thus, the present article presents a unique list of examples of age-appropriate lifeworld challenges for exemplary use in secondary school aiming at the pupils' general development and education.